2008
DOI: 10.1111/j.1525-139x.2008.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Placement of a Catheter through the Struts of a Previously Placed Stent for Maintenance Hemodialysis: A Case Report

Abstract: Venous accesses for hemodialysis are beset with thrombosis and stenosis, often resulting in loss of central venous access. We report a case in which an alternate access was created by placement of hemodialysis catheter into the central vasculature by penetrating a stent previously placed in the stenosed right brachio-cephalic vein. To our knowledge, this is the first such report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…We deployed two stents through this dilated opening in the strut of the IVC stent into the portal vein through the liver parenchyma, with one overlapping the other. Strutplasty was also used to place a dialysis access through a previously placed stent in the brachiocephalic vein [9].…”
Section: Discussionmentioning
confidence: 99%
“…We deployed two stents through this dilated opening in the strut of the IVC stent into the portal vein through the liver parenchyma, with one overlapping the other. Strutplasty was also used to place a dialysis access through a previously placed stent in the brachiocephalic vein [9].…”
Section: Discussionmentioning
confidence: 99%
“…They successfully cannulated the internal jugular vein on the first attempt in 86.7% of patients and at a significantly lower complication rate using ultrasound guidance. Joseph et al (11) reported the success of engaging in a team approach for vascular access management in a complex case scenario related to the placement of a tunneled catheter through a totally occluded stent in the right brachiocephalic vein. These reports provide evidence that nephrologists in India are working within their circumstances to provide the best care possible to their patients.…”
Section: Procedures Performed By Nephrologists In Indiamentioning
confidence: 99%